2012
DOI: 10.1111/j.1365-3024.2012.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Human chorionic gonadotrophin (hCG) enhances immunity against L. tropica by stimulating human macrophage functions

Abstract: During pregnancy, there are important changes in hormone levels such as the huge production of human chorionic gonadotropin (hCG), which is supposed to influence the immune system. The aim of this study was to investigate the effect of hCG on immune response against Leishmania, through the evaluation of the functions of human macrophages infected with L. tropica. This study demonstrated that hCG significantly increased the NO production by rHu-IFNγ-primed macrophages then infected with L. tropica, which was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Menzies and colleagues recently suggested an involvement of P4 in the regulation of genes associated with alternative macrophage activation (44). By contrast, hCG treatment of human and murine IFN-γ-primed macrophages resulted in increased production of nitric oxide, reactive oxygen species, IL-6 and IL-12p40, and enhanced phagocytosis of apoptotic cells (45, 46). However, hCG treatment of murine IFN-γ-primed macrophages did not affect the induction of allogeneic T cell proliferation (45).…”
Section: Hormonal Influence On Immune Cells During Pregnancymentioning
confidence: 89%
“…Menzies and colleagues recently suggested an involvement of P4 in the regulation of genes associated with alternative macrophage activation (44). By contrast, hCG treatment of human and murine IFN-γ-primed macrophages resulted in increased production of nitric oxide, reactive oxygen species, IL-6 and IL-12p40, and enhanced phagocytosis of apoptotic cells (45, 46). However, hCG treatment of murine IFN-γ-primed macrophages did not affect the induction of allogeneic T cell proliferation (45).…”
Section: Hormonal Influence On Immune Cells During Pregnancymentioning
confidence: 89%
“…In addition, hCG also regulates the immune rejection at the maternal-fetal interface during the embryo implantation window (30). Some studies believe that hCG plays a role in regulating endometrial immune tolerance by regulating the balance between th1/th2 cells and inhibiting the maternal immune rejection of embryos (31). Some scholars have found that hCG can improve the immunosuppressive function of regulatory T cells by increasing the number of transcription factor Foxp3 (32).…”
Section: Lh Bmentioning
confidence: 99%
“…This M1 to M2 cell shift seems to be partially fostered by hCG as indicated in human and mouse experimental settings (81,82) (Figure 1C). On the other hand, hCG stimulates proinflammatory functions in human monocytes and macrophages (83,84) suggesting that in case of an infection, hCG helps to protect the fetus from being attacked. Notably, human placental macrophages are able to produce high amounts of the pro-inflammatory cytokine IL-1 which in turn stimulates hCG secretion by human trophoblast cells (85) proposing a reciprocal interrelationship between macrophages and hCG during pregnancy.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%